2002
DOI: 10.3386/w8903
|View full text |Cite
|
Sign up to set email alerts
|

Can the New Deal's Three R's Be Rehabilitated? A Program-by-Program, County-by-County Analysis

Abstract: We examine the importance of Roosevelt's "relief, recovery, and reform" motives to the distribution of New Deal funds across over 3,000 U.S. counties, program by program. The major relief programs most closely followed Roosevelt's three R's. Other programs were tilted more in favor of areas with higher incomes. For all programs spending for political advantage in upcoming elections was a significant factor. Roosevelt's successful reelections were based on developing specific programs for a broad range of const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
4

Relationship

6
2

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 44 publications
(21 reference statements)
1
68
0
Order By: Relevance
“…Studies of the allocation of New Deal spending have found some evidence that states with a more volatile presidential vote received more federal support (Wright, 1974;Wallis, 1987Wallis, , 1996Fleck, 1999;Fishback, et al, 2003).…”
Section: Previous Literaturementioning
confidence: 99%
“…Studies of the allocation of New Deal spending have found some evidence that states with a more volatile presidential vote received more federal support (Wright, 1974;Wallis, 1987Wallis, , 1996Fleck, 1999;Fishback, et al, 2003).…”
Section: Previous Literaturementioning
confidence: 99%
“…4 See Wright (1974), Wallis (1987Wallis ( , 1998Wallis ( , 2001), Anderson and Tollison (1991), Couch and Shughart (1998), Fleck (1999a, 1999c, 2001a, 2001b, and Fishback, Kantor, and Wallis (2003). Powell's (2003) recent book paints a negative picture of the effectiveness of the New Deal, while citing many of these studies.…”
Section: Equation (22) Equation 22 Can Then Be Rewritten As the Chmentioning
confidence: 99%
“…The explicit goal of the AAA program was to raise farmers' incomes, although landowners in particular tended to be the disproportionate beneficiaries. The empirical literature on the geographic distribution of programmatic New Deal spending at the county level suggests that relief spending was distributed to areas where there was relatively more economic distress, while the public works programs responded to higher unemployment (see Fishback, Kantor, and Wallis 2003).…”
Section: Data Considerationsmentioning
confidence: 99%
“…For a good description of relief activity within a state, see Fearon (2007) for the state of Kansas. A large number of statistical studies analyze the political economy of the distribution of the New Deal relief funds, including most recently Fleck (1999aFleck ( , 1999bFleck ( , 2001aFleck ( , 2008, Wallis (1987Wallis ( , 1991Wallis ( , 1998Wallis ( , and 2001 and Fishback, Kantor, and Wallis (2003), which summarizes results for a large number of studies of all New Deal programs. See also Wright (1974).…”
Section: Relief and Poverty Programsmentioning
confidence: 99%